Preliminary design of an Initial Test of Integrated Skills within TRADILEX: an ongoing project on the validity of audiovisual translation tools in teaching English - Pilar Couto-Cantero; Mariona Sabaté-Carrové; María Carmen Gómez Pérez (Research in Education and Learning Innovation Archives)
This article shows the preliminary design process for a tailor-made Initial Test of Integrated Skills (ITIS) specially adapted to the needs of TRADILEX, a project (2020-2023) funded by the Spanish Ministry of Science, Innovation and Universities to study the scope and validity of using audiovisual translation (AVT) tools to develop communicative competence in a foreign language. We also design a complete virtual AVT-based teaching platform that will help to promote faster and better EFL learning. In this paper we present one of the project’s initial stages, i.e. the ITIS design and the methodological framework for the design process from draft stage to final product. The draft pilot ITIS was tested by specialists, who produced a series of reports and anticipated several potential problems that occurred when the test was carried out. We pay special attention to the changes and improvements made to the draft ITIS as well as its three-stage process and remedial measures. The validity of the ITIS is currently being tested with a pilot group. The ITIS will be complemented with a Final Test of Integrated Skills (FITIS), which is currently underway.